The Influence of a Family Support Group on the Motivation of Drug Users Undergoing the Rehabilitation Process in Syifa Medika Clinic Addiction Rehabilitation Center - Joko Sutrisno; A Fawzi; Saifullah Saifullah (Universitas Airlangga, 2020)
Introduction: One form of intervention is the rehabilitation of drug users. This takes time, money and effort. It takes a family support group to ensure that the drug users are motivated. The aim of this research was to determine the influence of family support on the motivation of the drug users undergoing rehabilitation at Syifa Medica Clinic in Kediri.Methods: This study used a correlation analytical design and a cross-sectional approach. The population of this research consisted of all of the drug users undergoing the rehabilitation process with the 25 samples taken using the accidental sampling technique. The independent variables of family support and motivation are needed to undergo rehabilitation process. These variables were collected using a questionnaire and analyzed using the Spearman Rank test.Results: The results of this study show that most of the respondents have positive support, totaling 15 respondents (60%). Nearly half had low motivation, totaling 12 respondents (40%). No family support relationships were found to pair with the motivation to undergo rehabilitation among the drug users (Spearman, p = 0,000 < 0,05: Ho is rejected). The level of relations included ‘quite strong’ and ‘positive’ (+0,732).Conclusion: Family support allows the drug users to obtain emotional closeness, causing a sense of security and a high motivation to undergo rehabilitation.